The functioning of new legal regulations on health care for pupils in the practice of an educational setting nurse - Pluta, Agnieszka; Marzec, Alicja (Nursing in the 21st Century, 2021)
THE FUNCTIONING OF NEW LEGAL REGULATIONS ON HEALTH CARE FOR PUPILS IN THE PRACTICE OF AN EDUCATIONAL SETTING NURSEIntroduction. Recently, much attention and interest have been devoted to the health care of school children in Poland. The current status was critically assessed and new legal regulations were prepared to bring about improvement.Aim. The aim of this paper is to present the functioning of current legal regulations in the field of health care for school children in the practice of an educational setting nurse.Discussion. The new law gives every student of public and private, primary and secondary schools the right to seek the care of a nurse and a dentist. It specifies the principles of cooperation and exchange of information between medical staff, parents, school management and authorities running the facility. Health care for a student in a school environment is preventive, focused on maintaining health, early detection of diseases, treatment, care and prevention of disability.Conclusions. The nurse is a direct health care provider and is also assigned the role of coordinator of preventive care over the school student. However, school nursing practice entails many organizational difficulties on the part of the school environment, parents/ legal guardians, as well as the students themselves. New regulations, their frequent updates and amendments, and inconsistencies in various documents force nurses to keep track of the revisions in order not to exceed their competence in practice. The nurse is prepared for professional practice in terms of expertise and direction and is able to competently fulfill the difficult role of a child care coordinator in a school environment.